2020
DOI: 10.1186/s12966-020-00949-0
|View full text |Cite
|
Sign up to set email alerts
|

Cultural adaptation of ‘Healthy Dads, Healthy Kids’ for Hispanic families: applying the ecological validity model

Abstract: Background: Healthy Dads Healthy Kids (HDHK) is a unique lifestyle obesity intervention for fathers and children that demonstrated weight loss among the fathers and behavior change among fathers and children in Australia. The program is gender-tailored to specifically target fathers for weight loss and 5-12 year old children for obesity prevention. The aim of this formative study was to examine an Expert Panel's and Hispanic Family Panel's perceptions about the program and suggestions for the cultural adaptati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…Additionally, investigators should consider the evaluation of additional family-level contextual factors that may impact obesity-related outcomes and behaviors [ 56 ]. For example, O’Connor et al, assessed family functioning as it has been shown that improving a family’s ability to work and communicate together can improve the family’s ability to participate and make changes to health behaviors as a family unit [ 58 , 59 ]. Similar reviews of family-based obesity prevention strategies have also reported that studies to date do not adequately examine how family factors mediate treatment effects [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, investigators should consider the evaluation of additional family-level contextual factors that may impact obesity-related outcomes and behaviors [ 56 ]. For example, O’Connor et al, assessed family functioning as it has been shown that improving a family’s ability to work and communicate together can improve the family’s ability to participate and make changes to health behaviors as a family unit [ 58 , 59 ]. Similar reviews of family-based obesity prevention strategies have also reported that studies to date do not adequately examine how family factors mediate treatment effects [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, intervention strategies should consider the SDoH that may limit disease prevention opportunities and health behaviors that may be leveraged or addressed within interventions to increase engagement and adherence [ 64 ]. About half of the articles included in this review addressed SDoH through content focused on determinants such as immigration stress and access to care or by having research staff call families to discuss barriers to program participation, language barriers, and acculturation [ 58 , 65 , 66 , 67 ]. For example, Crespo et al used group sessions with promotoras and clinic providers to improve patient-provider communication and address barriers to care [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past years, the adaption of existing evidencebased tools to different realities have received greater attention (39,40) . When the ELANS started, an expertise panel provided guidance to evaluate diet and other lifestyle behaviours for policy-making.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, O'Connor and colleagues 30,31 are leading a translation of the Healthy Dads, Healthy Kids (HDHK) program for Latino fathers and their children in Houston, Texas. Morgan et al 26,27 originally developed HDHK as an obesity treatment program for predominantly White fathers and their children in Australia and demonstrated success in efficacy and effectiveness trials.…”
Section: Motivation and Maintenancementioning
confidence: 99%
“…Although adapting a program can be difficult, their HDHK translation will generate valuable insights for supporting and sustaining behavior change with Latino fathers. 30,31…”
Section: Motivation and Maintenancementioning
confidence: 99%